4(-y+2)=-1

Simple and best practice solution for 4(-y+2)=-1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(-y+2)=-1 equation:


Simplifying
4(-1y + 2) = -1

Reorder the terms:
4(2 + -1y) = -1
(2 * 4 + -1y * 4) = -1
(8 + -4y) = -1

Solving
8 + -4y = -1

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-8' to each side of the equation.
8 + -8 + -4y = -1 + -8

Combine like terms: 8 + -8 = 0
0 + -4y = -1 + -8
-4y = -1 + -8

Combine like terms: -1 + -8 = -9
-4y = -9

Divide each side by '-4'.
y = 2.25

Simplifying
y = 2.25

See similar equations:

| X/3=70 | | N^10/7 | | 2m+-3m-8=26 | | Px+Q=X+1 | | 2x+4(2x+8)=10x+32 | | 1+8x^2+x^4= | | 90=(4x+12)+(6x+8) | | 4In(2x+3)=11 | | .15x+x=97.75 | | 4m+m=-90 | | (x+12)(x-7)=0 | | [8x]=28 | | .25(x+4)=41 | | 7/6=x/5 | | (7/28)=(3/x) | | 3x+24=4-10 | | 3(a+1)=5(a-1) | | x^3-2x^2-09+18=0 | | -112/16 | | 5x(3x-5)(x+1)=0 | | y=e^2x+17 | | Y=2x+a | | (9a-3)/3 | | Bj+m=j | | 16[x-3]=-80 | | 3d+2=12 | | X*.0147=(X-67) | | 11=3u-13 | | 11=3u+13 | | (x-67)=x*1.47 | | 6d+(5.5)=2d-(6.5) | | 6d+5.5=2d-(6.5) |

Equations solver categories